(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is a common Gynecological condition marked by anovulation and hyperandrogenism, affecting 7-8% of reproductive-age women. It’s a leading cause of treatable infertility. Many PCOS patients also show metabolic syndrome signs like insulin resistance, obesity, and dyslipidemia. Objective: To assess the insulin resistance in polycystic ovary syndrome patients. Methods: This was a case-control study that was conducted in the Department of Obstetrics & Gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2015 to December 2016. This study included 51 women aged 20-35 with polycystic ovary syndrome (PCOS). Data analysis was performed with MS Office tools and SPSS Version 23.0. Results: Among the total participants, the mean s. testosterone was 1.8±0.9 ng/ml and D2 s. LH was 12.7±6.7 mIU/mL; the difference was statistically significant (p<0.05). PCOS patients with HOMA-IR >3.2 had higher testosterone, LH, and insulin levels compared to those with HOMA-IR <<3.2. FSH levels did not differ significantly (p>0.05). Insulin resistance analysis revealed mean fasting insulin of 27.3± 10.7 U/ml, fasting blood sugar of 5.1 ± 0.8 mmol/L, and HOMA-IR at 4.1 +1.3. These values were statistically significant (p<0.05). Conclusion: The probability of developing insulin resistance is significantly greater in women with Polycystic Ovary Syndrome (PCOS) compared to women without PCOS. PCOS patients with insulin resistance are at increased risk of long-term complications like type 2 diabetes mellitus, hypertension, dyslipidemia, CAD, and gestational diabetes mellitus. J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 29-34